2003
DOI: 10.1037/0893-164x.17.4.277
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety, Negative Affectivity, and Substance Use Among High School Students.

Abstract: The literature regarding the relationship between adolescent social anxiety and substance use is sparse, and available studies have produced discrepant results. Similarly, negative affectivity is a mood-dispositional dimension that is infrequently considered in studies of substance use. The authors used dispositional structural equation modeling to examine the concurrent relationships of social anxiety and negative affectivity with adolescent substance involvement among 724 students in 1 southern California hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 48 publications
7
47
0
Order By: Relevance
“…We hypothesized that expectancies for not drinking would strongly differentiate individuals who initiate alcohol use from youth who maintain abstinence. Because of differences found in the literature regarding types of negative affect (e.g., Crum et al, 2008;Myers et al, 2003), we hypothesized that depression would be associated with increased risk for alcohol initiation, whereas social anxiety would be associated with decreased risk for alcohol-use initiation. Additionally, we hypothesized that expectancies for not drinking and perceptions of peer drinking would partially mediate the relationships between sensation seeking, negative affect, and the initiation of alcohol use.…”
Section: Current Studymentioning
confidence: 99%
See 3 more Smart Citations
“…We hypothesized that expectancies for not drinking would strongly differentiate individuals who initiate alcohol use from youth who maintain abstinence. Because of differences found in the literature regarding types of negative affect (e.g., Crum et al, 2008;Myers et al, 2003), we hypothesized that depression would be associated with increased risk for alcohol initiation, whereas social anxiety would be associated with decreased risk for alcohol-use initiation. Additionally, we hypothesized that expectancies for not drinking and perceptions of peer drinking would partially mediate the relationships between sensation seeking, negative affect, and the initiation of alcohol use.…”
Section: Current Studymentioning
confidence: 99%
“…Multiple studies have identified a relationship between negative affect and increased substance use during adolescence (Colder and Chassin, 1997;Myers et al, 2003;Shoal and Giancola, 2003;Stice et al, 1998), suggesting that individuals use substances to alleviate or cope with negative affect (Sher and Trull, 1994). Several researchers, however, have found this relationship to be negative or inconclusive (Brook et al, 1986;McGue et al, 2001;Stice et al, 1998;White et al, 1986).…”
Section: Negative Affectmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding support for SP symptoms as a protective factor, Tomlinson and Brown (2012) found that among a sample of eighth-grade students, SP symptoms were signifi cantly associated with less frequent drinking at parties. Similarly, Myers et al (2003) found that among a sample of high school students, those with higher SP symptoms were less likely to report substance use, including alcohol, tobacco, and marijuana use. In contrast, recent studies demonstrate more complex relationships between SP symptoms and alcohol use.…”
mentioning
confidence: 99%